Aerodynamic optimisation of civil aero-engine nacelles by dimensionality reduction and multi-fidelity techniques - Tejero, Fernando; MacManus, David G.; Hueso Rebassa, Josep; Sánchez-Moreno, Francisco; Goulos, Ioannis; Sheaf, Christopher T. (Unknown, 2022)
Aerodynamic shape optimisation is complex due to the high dimensionality of the problem, the associated nonlinearity and its large computational cost. These three aspects have an impact on the overall time of the design process. To overcome these challenges, this paper develops a method for transonic aerodynamic design with dimensionality reduction and multi-fidelity techniques. It is used for the optimisation of an installed civil ultra-high bypass ratio aero-engine nacelle. As such, the effects of airframe-engine integration are considered during the optimisation routine. The active subspace method is applied to reduce the dimensionality of the problem from 32 to 2 design variables with a database compiled with Euler CFD calculations. In the reduced dimensional space, a co-Kriging model is built to combine Euler lower-fidelity and RANS higher-fidelity CFD evaluations. Relative to a baseline aero-engine nacelle derived from an isolated optimisation process, the proposed method yielded a non-axisymmetric nacelle configuration with an increment in net vehicle force of 0.65% of the nominal standard net thrust. This work demonstrates that the developed methodology enables the optimisation of complex aerodynamic problems.